Characteristics and outcomes of pediatric testicular yolk Sac tumor - Li, Maoxian; Wang, Jinkui; Wang, Jianyu; Zhang, Deying; Hua, Yi; Liu, Feng; Lu, Peng; Liu, Junhong; Liu, Xing; Lin, Tao; Wei, Guanghui; He, Dawei (Frontiers in Pediatrics, 2022)
Purpose: Pediatric testicular yolk sac tumor is a rare malignant germ cell tumor, there is a lack of large clinical studies. The purpose of this study is to summarize the clinical characteristics of pediatric testicular yolk tumor and evaluate the prognostic factors. Materials and Methods: The medical records of children with testicular yolk sac tumor in one pediatric medical center in China from January 2005 to January 2021 were retrospectively investigated. Data were collected regarding clinical characteristics, treatment and prognosis. Results: 109 patients with a median diagnosed age of 18 months (range 2-69) were included in this study; of them 100 were diagnosed as Stage I, 6 as Stage II and 3 as Stage IV. All patients underwent radical orchiectomy, and 61 of them underwent postoperative chemotherapy. The mean follow-up time was 61.3 months(range 3-259), during that time, 8 patients relapsed. The five-year overall survival was 90.6%(95% CI 84.6%-96.7%). The univariate Cox regression analysis found disease stage, relapse, maximum tumor diameter, and alpha-fetoprotein returned to normal within 2 months postoperative as risk factors for survival (HR was 25.43, 26.43, 1.48 and 0.08, respectively, p <0.05), and multivariate Cox regression analysis suggested that higher disease stage and relapse were independently adverse factors for survival (HR was148.30 and 94.58, respectively, p <0.05). Conclusions: The prognosis of pediatric testicular yolk sac tumor is generally excellent. Higher disease stage and relapse could predict a poor prognosis. Individualized management of children with testicular yolk sac tumor according to risk classification is feasible.